Stability of hepatitis C virus (HCV) RNA levels among interferon‐naïve HIV/HCV‐coinfected individuals treated with combination antiretroviral therapy1. Issue 6 (27th March 2013) - Grint, D; Peters, L; Reekie, J; Soriano, V; Kirk, O; Knysz, B; Suetnov, O; Lazzarin, A; Ledergerber, B; Rockstroh, JK; Mocroft, A; ,
Abstract : Objectives: Infection with hepatitis C virus (HCV) is a major cause of chronic liver disease. High HCV RNA levels have been associated with poor treatment response. This study aimed to examine the natural history of HCV RNA in chronically HCV/HIV‐coinfected individuals. Methods: Mixed models were used to analyse the natural history of HCV RNA changes over time in HIV‐positive patients with chronic HCV infection. Results: A total of 1541 individuals, predominantly White (91%), male (73%), from southern (35%) and western central Europe (23%) and with HCV genotype 1 (58%), were included in the analysis. The median follow‐up time was 5.0 years [interquartile range (IQR) 2.8 to 8.3 years]. Among patients not on combination antiretroviral therapy (cART), HCV RNA levels increased by a mean 27.6% per year [95% confidence interval (CI) 6.1−53.5%; P = 0.0098]. Among patients receiving cART, HCV RNA levels were stable, increasing by a mean 2.6% per year (95% CI −1.1 to 6.5%; P = 0.17). Baseline HCV RNA levels were 25.5% higher (95% CI 8.8 to 39.1%; P = 0.0044) in individuals with HCV genotype 1 compared with HCV genotypes 2, 3 and 4. A 1 log HIV‐1 RNA copies/mL increase in HIV RNA was associated with a 10.9% increase (95% CI 2.3 to 20.2%; P = 0.012) in HCV RNA. Conclusions: While HCV RNA levels increased significantly in patients prior to receiving cART, among those treated with cART HCV RNA levels remained stable over time.